Effect of Different Concentrations of Titanium Dioxide Nanoparticles on the Potential Barrier of Organic Device (European Journal of Formal Sciences and Engineering, 2021)
Present work has studied potential barrier of Phenosafranin dye based organic device and has observed influence of different concentrations of titanium dioxide nanoparticles on this parameter. We have made different devices by taking different weight ratios of the dye – nanoparticles blend which are 1:1, 1:2, 1:3 and 1:4. These organic devices have been formed by varying the concentrations of titanium dioxide nanoparticles keeping same dye content. One device is also formed without any nanoparticle to compare influence of nanoparticle on potential barrier of the device. These devices are formed by sandwiching the dye – nanoparticle blend in between the Indium Tin Oxide coated glass and Aluminium coated mylar sheet. The potential barrier is measured from device’s I-V plot and also by Norde function. These two methods remain in good agreement showing that potential barrier is mostly decreased when the concentration of the titanium dioxide nanoparticles is highest in the blend of Phenosafranin dye and titanium dioxide nanoparticles. The ratio of dye –nanoparticle blend of 1:4 shows lowest potential barrier and it is highest when Phenosafranin dye based organic device is made without any nanoparticle. The reduced potential barrier in the presence of higher concentration of nanoparticles can be ascribed to improved filling of traps. Lowered potential barrier at metal – organic contact will improve the charge flow resulting in better performance of the device.
Keywords: Metal – Organic Dye Interface; Norde Function; Potential Barrier; Phenosafranin Dye; Titanium dioxide Nanoparticles